2016
DOI: 10.3844/ajabssp.2016.35.44
|View full text |Cite
|
Sign up to set email alerts
|

Quality Herbage Production of Dwarf Napiergrass with Italian Ryegrass Cropping under Digested Effluent Application in Southern Kyushu, Japan

Abstract: Digested effluent produced by a biogas-plant contains essential plant nutrients to solve the treated and disposal problems of livestock manure. Dwarf variety of late-heading type (dwarf) napiergrass as a perennial summer crop and intercropping of over-sown Italian ryegrass as an annual winter crop were applied to 3 levels of digested effluent in southern Kyushu from 2007 to 2009. Digested effluent revealed so effective fertilizer as chemical one to increase dry matter yield, wintering ability and forage qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Nutritional quality is strongly influenced by management practices and age at harvest but, on average, Napier grass is considered to contain 9% CP, 20% DM, 70% NDF, 50% ADF, 9% ash and 6% lignin in samples taken from 10-15 week old plants [74,75]. Apart from genetics, the nutritional qualities of forages are influenced by many factors including the climate [76], soil nutrition [77], season and grazing pressure [78], management [65,79,80] and fertilizer application [81]. Consequently, great care should be taken to determine the optimum time when planning to harvest or graze Napier grass in order to maximize both yield and nutritional qualities [82].…”
Section: Nutritional Qualitiesmentioning
confidence: 99%
“…Nutritional quality is strongly influenced by management practices and age at harvest but, on average, Napier grass is considered to contain 9% CP, 20% DM, 70% NDF, 50% ADF, 9% ash and 6% lignin in samples taken from 10-15 week old plants [74,75]. Apart from genetics, the nutritional qualities of forages are influenced by many factors including the climate [76], soil nutrition [77], season and grazing pressure [78], management [65,79,80] and fertilizer application [81]. Consequently, great care should be taken to determine the optimum time when planning to harvest or graze Napier grass in order to maximize both yield and nutritional qualities [82].…”
Section: Nutritional Qualitiesmentioning
confidence: 99%
“…In general, DS is an efficient N source for plants with the potential to improve crop and forage yields and soil properties (Arthurson 2009). It has been reported that the effect of DS fertilizer is similar to that of mineral fertilizer in maize (Chantigny et al 2008), a maize-Italian ryegrass cropping system (Idota et al 2013), dwarf Napier grass (Hasyim et al 2010(Hasyim et al , 2014(Hasyim et al , 2016 and orchardgrass (Matsunaka et al 2003). However, the effect of DS application on zoysia grass has not been studied.…”
Section: Introductionmentioning
confidence: 99%